Factors for Chronic Energy Deficiency (KEK) in Pregnant Women: Faktor Kejadian Kurang Energi Kronik (KEK) Pada Ibu Hamil - Silfia, Niluh Nita; Maineny, Arie; Yustika, Yustika (Poltekkes Kemenkes Palu, 2022)
Background: Pregnant Women with Chronic Energy Deficiency (KEK) are undernourished status due to an imbalance between intake and energy expenditure. The results of Riskesdas (2018) the prevalence of KEK is 17.3%. Case data of pregnant women with KEK at the Lariang Health Center, Lariang District in 2020 as many as 41 people. Objective: To determine the factors of pregnant women with chronic lack of energy at the Lariang Health Center in 2020 (age factors, family income and parity). Methods: This research method is case control with a retrospective approach. The sample in this study was 80 respondents with a random sampling technique. The tools used in this study were observation sheets and visit books for pregnant women. Research time 1 – 20 April 2021. Analysis of univariate and bivariate data with chi-square statistical test. Results: There are 47.5% have age 35 years. There are 60% have family income < Rp. 2,571,328. There are 55% having parity at risk of 1 and 3. The results of the Chi Square test show that there is a relationship between the age of pregnant women (p value = 0.004), there is a relationship between family income of pregnant women (p value = 0.000) and there is a relationship between parity of pregnant women (p value = 0.002) with Chronic Energy Deficiency. Conclusion: There is a relationship between age at risk, low family income and parity at risk of pregnant women with chronic energy deficiency at the Lariang Health Center. Suggestions that can be given are to provide counseling about the dangers of KEK to pregnant women as well as knowledge of the importance of nutrition, and pregnancy checks by health workers.